Analisis Tingkat Kesadaran 5R dan Tingkat Bahaya Lingkungan Terhadap Kinerja Karyawan - Mauludia, Putri; Putra, M Hengki Riawan; Utomo, Eko Budi; Hadidjija, Kusno (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of 5S awareness and environmental hazard levels on employee performance in a manufacturing company. Implementing the 5S concept is crucial for creating a clean, orderly, and efficient environmental hazard level, while controlling environmental hazard levels aims to minimize the risk of accidents and occupational diseases. The research method used was a quantitative approach, with data collected through questionnaires distributed to 100 employee respondents. Data analysis was conducted using multiple linear regression to determine the relationship and influence of the independent variables on the dependent variable. The results showed that 5S awareness had a positive and significant effect on employee performance, while environmental hazard levels had a negative and significant effect. These findings indicate that higher 5S awareness and lower environmental hazard levels tend to improve employee performance. Companies need to increase 5S socialization and training and strengthen occupational safety systems to create a productive and safe environmental hazard level.